Unraveling the literature chaos around free ammonia inhibition in anaerobic digestion. (January 2020) - Capson-Tojo, G.; Moscoviz, R.; Astals, S.; Robles, Á.; Steyer, J.-P.
Abstract: This review aims at providing a unified methodology for free ammonia nitrogen (FAN) calculation in anaerobic digesters, also identifying the factors causing the huge disparity in FAN inhibitory limits. Results show that assuming ideal equilibria overestimates the FAN concentrations up to 37% when compared to MINTEQA2 Equilibrium Speciation Model, used as reference. The Davies equation led to major improvements. Measuring the concentrations of NH4 +, Na + and K + was enough to achieve major corrections. The best compromise between complexity and accuracy was achieved with a novel modified Davies equation, with systematic differences in FAN concentrations of 2% when compared to MINTEQA2. Applying this modified Davies equation, data from the literature (1590 data points from over 50 scientific studies) were used to recalculate FAN inhibitory limits using a clustering approach. This procedure allowed to link inhibition resilience with operational conditions and microbial communities, providing also generalized values of inhibitory constants. The results showed that pH and temperature are the main factors affecting FAN inhibition, with thermophilic systems having a higher resilience towards FAN inhibition. The clustering results showed that Methanosaeta -dominated reactors have the lowest resilience towards FAN, verifying the relatively low inhibition limits for acetoclastic archaea. Mixotrophic Methanosarcina dominated at intermediate FAN concentrations, being more resistant than Methanosaeta but less resilient than hydrogenotrophic archaea. Methanoculleus appeared as the most resilient methanogen. This article provides general guidelines for accurate FAN calculation, explaining also how FAN resilience relates to the operational conditions and the microbial communities, underlying the importance of microbial adaptation. Graphical abstract: Image 1 Highlights: The ideal equilibrium equation overestimates the FAN concentration up to 37%. The Davies equation considering few ions leads to a mayor improvement in most cases. A more accurate modified Davies equation is proposed. pH and temperature as main factors determining the resilience to FAN inhibition. Methanosaeta replaced by hydrogenotrophic archaea at high FAN concentrations.